The Prevalence and Association of Cyberbullying and Depression in the Malaysian Adolescent Population During the COVID-19 Pandemic - Pang, Khong Yun *; Ku, Wen Li; Teng, Jaclyn Hui Jie *; Ling, Philip Oon Hun; Ooi, Pei Boon * (Taylor and Francis Group, 2023)
The COVID-19 pandemic has brought about the implementation of distance and online learning in educational settings, causing cyberbullying to become a rising issue as Internet use has become a necessity among adolescents for their learning and schooling during the pandemic. This increased use of the Internet due to the current mode of learning has led to the emergence of more frequent experiences of depression, as there is a great lack of social interaction among school adolescents. Therefore, this study seeks to examine the prevalence of cyberbullying and depression and the association between the two among Malaysian adolescents during the COVID-19 pandemic period. A cross-sectional study using convenience was carried out via Survey Monkey, reaching a total of 1591 respondents in Malaysia. The data collected was then analyzed using the binary logistic regression test with single independent variable. Based on the survey results, 281 (17.6%) respondents self-reported to having severe depression, while 726 (45.6%) respondents self-reported to having no depression. Incidences of cyberbullying were reported to have occurred among 619 (38.9%) respondents, with daily incidences being reported as happening the most frequent (16.5%), followed by a couple of times a month (14.1%), and once a month (13.1%). It was also found that cyberbullying experiences during the pre-pandemic (OR = 1.41, 95%, C.I. = 1.003, 1.978) and post-pandemic periods (OR = 5.21, 95%, C.I. = 3.120, 8.690) are associated with depression. Additionally, females (OR = 2.94, 95%, C.I. = 2.388, 3.613) and those within the age group of 16 to 18 years (OR = 1.23, 95%, C.I. = 1.008, 1.503) achieve a high depression score. This study concludes that there is a high prevalence of cyberbullying and depression among Malaysian adolescents. Therefore, we urge for immediate interventions to be carried out to monitor the online activity, incidences of cyberbullying, and depression issues among Malaysian adolescents.